2020
DOI: 10.1039/d0ra08564b
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable separation of bio-based cadaverine based on carbon dioxide capture by forming carbamate

Abstract: Cadaverine carbamate, capturing the self-released carbon dioxide from the decarboxylation of l-lysine, is the green and sustainable separation of bio-based cadaverine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Our team is committed to researching biobased PDI. In our previous study, sugar from biomass was used as the raw material to produce 1,5-pentanediamine through fermentation, and PDI was subsequently synthesized from 1,5-pentanediamine using the phosgene method. , The resulting PDI adhesive exhibited excellent adhesion . In this study, biobased PDI was used as the raw material and 2-hydroxypropyl-trimethylisooctanoic acid ammonium salt (TMR) was employed as the catalyst to synthesize biobased PDI trimers.…”
Section: Introductionmentioning
confidence: 99%
“…Our team is committed to researching biobased PDI. In our previous study, sugar from biomass was used as the raw material to produce 1,5-pentanediamine through fermentation, and PDI was subsequently synthesized from 1,5-pentanediamine using the phosgene method. , The resulting PDI adhesive exhibited excellent adhesion . In this study, biobased PDI was used as the raw material and 2-hydroxypropyl-trimethylisooctanoic acid ammonium salt (TMR) was employed as the catalyst to synthesize biobased PDI trimers.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has created a complete, mature technology route for biobased PDI. First, we fermented biomass sugar to form l -lysine, then converted l -lysine into 1,5-pentanediamine or cadaverine by lysine decarboxylase, and finally synthesized PDI using 1,5-pentanediamine as the raw material. , We also found that PDI shows excellent adhesion performance when applied to adhesives . In this work, we used PDI as a raw material to synthesize the PDI isocyanurate trimer and allophanate-modified PDI isocyanurate trimer (PDI-T-M) by introducing butanediol, then removed the unreacted free PDI monomer to prepare PDI isocyanurate curing agents, and finally prepared 2K-PU coatings to verify the coating performances.…”
Section: Introductionmentioning
confidence: 99%